Estudo do potencial energético de briquetes produzidos a partir de resíduos agrícolas de casca de castanha de caju e bagaço da cana-de-açúcar - Vidal, Mariana de Souza (2018)
According to studies released by the Energy Research Company (EPE), Brazilian consumption by 2050 will triple, reaching 1,624 terawatt hour (Twh). However, the largest source of energy, such as hydroelectric power plants, is not as necessary as it is in some factors, including a water shortage. Dought that context, to guarantee all the energy that the scenario presented by the EPE study, is necessary for the 20 20, as well as the search for alternative sources of energy, with the new sources of investment that are being made. Among the alternatives to overcome this problem, has a biomass, source of clean and renewable energy, with greater potential for growth in recent years. For the withdrawal of the energy resource, we have the agro-industrial sector, producing a large amount of waste. On a daily basis, a large volume of waste is generated by the agroindustry, where the vast majority of them are disposed of in the environment, and can originate from environmental damages when they are being used as an energy source. Among the residues of sugarcane bagasse and a cashew nut shell, which were objects of study of the present work. To potentiate the use of biomass, it can be transformed into solid fuel, such as briquette, which is done by means of compaction techniques. After compaction, the work in question sought to analyze its energetic potentialities. To the, they were analyzed for the calorific superior power (PCS) of each briquette and the immediate analysis, where the the content of volatile, and the carbon fixed of each sample. The PCS of the nut shell was spectacular at around 18MJ / kg, a value that is burst when it was with the materials already used.